(3eNJUQ GdefJXe hedJbW GdedJRe dGHf GdLhRi GdeJhaj SfI (B597(3g`s - (3YdGA GdOjf Ydj Hf eMeO Hf eSYhO GdgQhi , GdTgjQ HGdedhi eUfac GdTGgQhOi GdHSWGeis; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s ((3fGUQ GdOjf GdLhgQi GdHcQj GdeUQj s)
(3ChdgG (B:s
(3PcQ NdGaI GdUOjb QVi Gddg Yfg hCMhGdg s
(3BNQgG (B:s
(3hdbO SejJ cJGHi gPG eNJUQ GdefJXe hedJbW GdedJRe hbVi gPG GdEJeGe Edi hbJ GdVMi jhe GdSHJ ZQI TgQ Gddg GdeMQe , SfI SHYjf hKeGfeGFI s
(3HgG WeSs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs